Deep brain stimulation reduces pain in children with dystonia, including in dyskinetic cerebral palsy. (9th May 2020) - Perides, Sarah; Lin, Jean‐Pierre; Lee, Geraldine; Gimeno, Hortensia; Lumsden, Daniel E; Ashkan, Keyoumars; Selway, Richard; Kaminska, Margaret
Abstract : Aim: To establish the prevalence of dystonic pain in children and their response to deep brain stimulation (DBS). Method: Dystonic pain was assessed in a cohort of 140 children, 71 males and 69 females, median age 11 years 11 months (range 3y–19y 1mo), undergoing DBS in our centre over a period of 10 years. The cohort was divided into aetiological dystonia groups: 1a, inherited; 1b, heredodegenerative; 2, acquired; and 3, idiopathic. Motor responses were measured with the Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS). Results: Dystonic pain was identified in 63 (45%) patients, 38% of whom had a diagnosis of cerebral palsy (CP). Dystonic pain improved in 90% of children and in all aetiological subgroups 1 year after DBS, while the BFMDRS motor score improved in 70%. Statistically significant improvement ( p <0.01) was noted for the whole cohort on the Numerical Pain Rating Scale ( n =27), Paediatric Pain Profile ( n =17), and Caregivers Priorities and Child Health Index of Life with Disabilities questionnaire ( n =48). There was reduction of pain severity, frequency, and analgesia requirement. Findings were similar for the whole cohort and aetiological subgroups other than the inherited heredodegenerative group where the improvement did not reach statistical significance. Interpretation: Dystonic pain is frequent in children with dystonia, including those with CP, who undergo DBS; this can be an important, realizable goal of surgery irrespective of aetiology. We encourage the use of multimodal approach in pain research to reduce the risk of bias. Abstract : This article is commented on by Frizon and Francisco on page 886 of this issue. Editor's Choice Pain is increasingly recognized in association with dystonia. Dystonic pain is disabling and not well understood. In addition to excess muscle contraction, impaired regulation of nociception may be implicated. My Editor's Choice for the August issue is this study documenting the effect of deep brain stimulation on pain experienced by children with dystonia who underwent the treatment for the motor disorder. Video Podcast: https://youtu.be/wa6nGhLI3_4